Implementation of Arabic Language Learning Media Using the Canva Application to Enhance Teachers’ Skills - Dedy Rizaldi; Hilmi (Barkah Publishing, 2026)
Arabic language learning in various educational institutions still faces challenges, particularly in terms of low instructional attractiveness and limited teacher skills in developing innovative learning media. Therefore, the use of digital technology is needed as a solution to improve the quality of learning. This study aims to analyze the implementation of the Canva application as a learning medium in improving teachers’ skills in Arabic language instruction. The method used is library research by reviewing various relevant scientific sources such as journals, books, and proceedings related to the research topic. The data analysis technique is conducted using a descriptive-analytical approach by synthesizing findings from previous studies. The results of the study indicate that the use of the Canva application contributes positively to improving teachers’ skills, especially in designing attractive, creative, and interactive learning media. In addition, Canva has also been proven to enhance students’ learning motivation through the presentation of more communicative visual-based materials. Thus, the implementation of Canva in Arabic language learning is an effective alternative in supporting technology-based learning in accordance with the demands of the digital era.